PERANCANGAN VIDEO ANIMASI 2D CERITA PUTRI MANDALIKA SEBAGAI UPAYA PELESTARIAN BUDAYA UNTUK ANAK SEKOLAH DASAR - Lalu Ikhwanul Satya Negara; Sultan Arif Rahmadianto; Didit Prasetyo Nugroho (Fakultas Sains Dan Teknologi Universitas Ma Chung, 2022)
One of the folklore in Lombok is the story of Putri Mandalika. Princess Mandalika is a princess who threw herself into the sea to avoid division between kingdoms. However, there is a lack of awareness for the younger generation in preserving folklore. For this reason, there are appropriate alternative media to introduce Putri Mandalika's story, one of them is animation video. The method used is a qualitative method. Qualitative data obtained through observation, interviews, and literature study. Animated video of Putri Mandalika story using a paper cut design style with 6 minutes 37 seconds duration.